Impact of E-commerce Performance on Economic Growth: Evidence in Vietnam - Pham, Minh Tien (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2025)
This paper examines the influence of the E-commerce performance on economic growth in provinces and cities of Vietnam. Indicating the further reliability over the Fixed Effects Model (FEM) and Random Effects Model (REM), the Ordinary Least Squares regression (OLS) is utilized for the study with the panel data set of 44/63 provinces and cities of Vietnam. The regression result reveals that E-commerce performance is significant and affects positively the economic growth in localities of Vietnam. The role of E-commerce performance is proved to be crucial when 1 unit increase of it will lead to 2.35% in economic growth. The research outcomes could be interpreted to be the policy implications for the provincial government to carry out the plans and strategies for the local economic development.